"Somehow the pathetic dumb suffering of these elderly people moves me more than anything": Caring for Elderly Holocaust Survivors in the Immediate Postwar Years. (22nd November 2018) - Stone, Dan
Abstract: Although a great deal has been written, primarily from a medical or psychological perspective, on the ways in which the Holocaust affected survivors' aging process, not much has been written about elderly survivors in the immediate postwar period. This article asks what we can know about elderly survivors, how they responded to their survival, and how they were cared for after liberation. It considers gender and social class, as well as specific caretaking needs. Despite efforts by relief organizations to recognize their plight, care regimens for the elderly were often individualized and thus isolating.